Computing the mechanical properties of alpine skis - Nordt, A. A.; Springer, G. S.; Kollar, L. P. (Sports Engineering, 1999)
Models were developed to calculate the mechanical properties of alpine skis. The skis considered are constructed of layers of materials which may include wood, foam, metal, plastics and fibre-reinforced composites. The ski may be manufactured with or without camber and sidecut. On the basis of the models, a computer code was written which yields the mass, bending and torsional stiffness distributions along the length, flex, twist, natural frequencies and the pressure distribution along the base of the ski. The computer code was verified by comparing the outputs of the code to laboratory data. The numerical results and the data were in good agreement lending confidence to the models and the supporting computer code.